The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/raq.12791
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in crustacean genomics and their potential application in aquaculture

Abstract: Genomic resources are increasingly being used to improve the production efficiency and profitability of aquaculture. Crustaceans are a large group of invertebrates that encompasses some of the most important farmed species in the aquaculture industry. However, very few crustacean genomes have been published although an aquaculture genome project was proposed as early as 1997. Breakthroughs in next‐generation and third‐generation sequencing technologies and the development of high‐complexity sequence assembly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 217 publications
0
5
0
Order By: Relevance
“…Currently, genome-wide association studies (GWAS) have been conducted based on chromosome-level genome reference mapping to identify genes associated with economically relevant traits such as growth, sex, disease resistance, and environmental adaptation. Resequencing and selection characterization have also confirmed that genes linked to growth and disease resistance are indeed selected for in artificial breeding [71].…”
Section: Gene Mappingmentioning
confidence: 81%
See 1 more Smart Citation
“…Currently, genome-wide association studies (GWAS) have been conducted based on chromosome-level genome reference mapping to identify genes associated with economically relevant traits such as growth, sex, disease resistance, and environmental adaptation. Resequencing and selection characterization have also confirmed that genes linked to growth and disease resistance are indeed selected for in artificial breeding [71].…”
Section: Gene Mappingmentioning
confidence: 81%
“…Of the 4683 scaffolds, 3275 were anchored to 44 pseudochromosomes, representing 87.34% of the genome assembly size. The L. vannamei genome was the first high-quality reference genome for penaeid shrimp, and since then, the strategy has been used to sequence most crustacean genomes, including various shrimp, crayfish, crabs, krill, isopods, and amphipods [10,71,79,82].…”
Section: Genome Assembly At Chromosome Levelmentioning
confidence: 99%
“…Exploring the reproductive patterns and mechanisms of A. parthenogenetica may contribute to understanding the evolutionary route of animal reproduction from the sea to land, and how Artemia adapt to environmental changes and maintain population stability. With the publication of the genome of Artemia franciscana [66,67] and the completion of whole-genome sequencing of A. parthenogenetica (data not shown, ARARC sequenced), it is possible to find more accurate and detailed molecular evidence to interpret the role of Artemia in the evolution of species at the omics level.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the genome architecture of this exceptionally invasive copepod species complex would provide fundamental insights into the genomic and evolutionary mechanisms facilitating their rapid habitat invasions [38,39]. However, high-quality genome resources have long been absent for most copepod groups [40,41]. Only four chromosome-level genome assemblies are available for copepods in the NCBI Genome database [42], namely for two parasitic copepods (Siphonostomatoida) and two species of the intertidal copepod Tigriopus (Harpacticoida).…”
Section: Introductionmentioning
confidence: 99%